2021
DOI: 10.1136/bcr-2021-243629
|View full text |Cite
|
Sign up to set email alerts
|

Case of Guillain-Barré syndrome following COVID-19 vaccine

Abstract: Guillain-Barré syndrome (GBS) is a rare immune-mediated disorder of the peripheral nerves. Although its cause is not fully understood, the syndrome often follows infection with a virus or bacteria, although in rare occasions, vaccination may precede GBS. We describe a case of a 62-year-old woman who presented with paraesthesia and progressive weakness of both lower limbs over 3 days. Clinical examination and investigation findings including lumbar puncture and nerve conduction studies were consistent with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
94
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(102 citation statements)
references
References 23 publications
0
94
0
8
Order By: Relevance
“…The Janssen COVID-19 vaccination fact sheet was recently updated by the Food and Drug Administration to include a warning about Guillain-Barré Syndrome associated with its vaccine [16,[20][21][22][23][24][25][26][27].…”
Section: Guillain-barré Syndrome Deve-lopmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The Janssen COVID-19 vaccination fact sheet was recently updated by the Food and Drug Administration to include a warning about Guillain-Barré Syndrome associated with its vaccine [16,[20][21][22][23][24][25][26][27].…”
Section: Guillain-barré Syndrome Deve-lopmentmentioning
confidence: 99%
“…Guillain-Barré Syndrome is believed to be triggered by an antecedent infection1,6 such as a viral infection (especially infl uenza, COVID-19, and Zika virus) [5][6][7][8][9][10], a gastrointestinal-related infection, bacterial infection such as Campylobacter jejuni [11][12][13], food poisoning, or from a reaction to a vaccine [14]. Approximately 9-11% of cases result in severe disability or death [12,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Since marketing authorization, cases of NA, FP/BP and GBS were reported with COVID-19 vaccines [4][5][6][7][8][9][10][11]. A recent pharmacovigilance study in VigiBase, the World Health Organization's (WHO) global database of suspected adverse drug reactions (ADRs) found that the reporting frequency of FP/BP with mRNA COVID-19 vaccines was similar to that with other viral vaccines [12].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, several transverse myelitis cases and other complications arising from COVID-19 vaccination, including thrombosis with thrombocytopenia syndrome (TTS), have been reported on CDC and FDA Vaccine Adverse Event Reporting System (VAERS) [12][13][14][15][16]. The FDA VAERS system has reported 45 cases of transverse myelitis as of 27 April 2021.…”
Section: Introductionmentioning
confidence: 99%